Kajian Morfosemantis Terhadap Serat Centhini - Junanah Junanah (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2010)
The article explains the deviation of Arabic language absorbed by Serat Centhini from linguistics point of view. Until now, there is an opinion that it has a deviation of the use of Arabic language in Serat Centhini. The study is important to conduct, for linguistically it implicates on the changes of sound, form and meaning of the Arabic absorbent in the Serat Centhini itself.